Photoalignment and photopatterning: New liquid crystal technology for displays and photonics - V. G. Chigrinov (Тонкие химические технологии, 2020)
Objectives. Since the end of the 20th century, liquid crystals have taken a leading position as a working material for the display industry. In particular, this is due to the advances in the control of surface orientation in thin layers of liquid crystals, which is necessary for setting the initial orientation of the layer structure in the absence of an electric field. The operation of most liquid crystal displays is based on electro-optical effects, arising from the changes in the initial orientation of the layers when the electric field is turned on, and the relaxation of the orientation structure under the action of surfaces after the electric field is turned off. In this regard, the high quality of surface orientation directly affects the technical characteristics of liquid crystal displays. The traditional technology of rubbing substrates, currently used in the display industry, has several disadvantages associated with the formation of a static charge on the substrates and surface contamination with microparticles. This review discusses an alternative photoalignment technology for liquid crystals on the surface, using materials sensitive to polarization of electromagnetic irradiation. Also, this review describes various applications of photosensitive azo dyes as photo-oriented materials. Results. The alternative photoalignment technology, which employs materials sensitive to electromagnetic polarization, allows to create the orientation of liquid crystals on the surface without mechanical impact and to control the surface anchoring force of a liquid crystal. This provides the benefits of using the photoalignment technology in the display industry and photonics—where the use of the rubbing technology is extremely difficult. The optical image rewriting mechanism is discussed, using electronic paper with photo-inert and photoaligned surfaces as an example. Further, different ways of using the photoalignment technology in liquid crystal photonics devices that control light beams are described. In particular, we consider switches, controllers and polarization rotators, optical attenuators, switchable diffraction gratings, polarization image analyzers, liquid crystal lenses, and ferroelectric liquid crystal displays with increased operation speed. Conclusions. The liquid crystal photoalignment and photopatterning technology is a promising tool for new display and photonics applications. It can be used for light polarization rotation; voltage controllable diffraction; fast switching of the liquid crystal refractive index; alignment of liquid crystals in super-thin photonic holes, curved and 3D surfaces; and many more applications.